Australia’s Foreign Policy Shift Towards China: An Examination of Domestic Politics in the Scott Morrison Administration - Ida Ayu Bulan Utami Arti (Universitas Warmadewa, 2026)
This study examines the development in Australia-China diplomatic relations, which changed dramatically during Prime Minister Scott Morrison’s term (2018-2022). Previously, the two countries had appeared to be very harmonious and bound by complementary economic relations through the Australia-China Free Trade Agreement in 2015. When Scott Morrison was successfully inaugurated as Prime Minister, Australia dared to shifts its foreign policy towards China in a confrontational and anti-China direction. Australia's confrontational and anti-China foreign policy is evaluated through three offensive decisions, including the prohibition investment and trade links with China, the restriction Chinese foreign students in Australia, and Australia's attacks on China at the multilateral level. Therefore, this study tries to analyze the elements driving changes in Australia's foreign policy towards China. This study aims to fill the analytical gap left by prior studies, focusing on domestic political considerations as a significant variable in driving changes in Australia's foreign policy towards China. This study takes a qualitative approach, with descriptive and comparative analysis methodologies used in the data processing process. By referring to and using Type III Neoclassical Realism Theory, this study found that the domestic factors influencing these changes were: 1) Scott Morrison’s policy perception and leadership outlook; 2) Australia’s strategic culture as a lens of policy imagination; 3) Australian public opinion and its constraining effect on policy choices; and 4) the Liberal-National Coalition party’s ideology and its role in shaping policy decisions.